P2-purinoceptors of two subtypes in the rabbit mesenteric artery: reactive blue 2 selectively inhibits responses mediated via the P2y-but not the P2x-purinoceptor. - Burnstock, G. (1987)
alpha,beta-Methylene ATP and ATP both produced concentration-dependent contractions of the isolated mesenteric artery of the rabbit that were not inhibited by reactive blue 2. In preparations where the tone had been raised with noradrenaline, ATP and 2-methylthio ATP, but not alpha,beta-methylene ATP, produced relaxations of the vessel. These relaxations were inhibited in the presence of reactive blue 2. Reactive blue 2 did not inhibit the contractions to noradrenaline, and only slightly inhibited relaxations to adenosine and acetylcholine. The rank order of potency of purine nucleotide analogues in contracting the vessel was: alpha,beta-methylene ATP greater than beta,gamma-methylene ATP = 2-methylthio ATP greater than ATP, and in relaxing the vessel at raised tone was: 2-methylthio ATP greater than ATP greater than beta,gamma-methylene ATP greater than alpha,beta-methylene ATP. It is concluded from this study that in the isolated mesenteric artery of the rabbit, purine nucleotides act via P2y-purinoceptors to cause the muscle to relax and via P2x-purinoceptors to cause the muscle to contract. The results also suggest that reactive blue 2 selectively inhibits responses mediated via the P2y-purinoceptor, at least within a limited concentration range.